"Pengaruh Kredibilitas Influencer Terhadap Niat Beli Gen Z Di Tokopedia" - Nasywa Nabila; Valentino C.H; Rosida P. Adam (Journal of Innovative and Creativity, 2025)
This study aims to analyze the effect of influencer credibility on Generation Z’s purchase intention on the Tokopedia e-commerce platform. Influencer credibility is measured through three dimensions: expertise, trustworthiness, and attractiveness. The study employs a quantitative method with a causal approach involving 30 Generation Z students from the Faculty of Economics and Business who actively use Tokopedia. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that influencer credibility has a significant simultaneous effect on purchase intention (F = 4.488; p = 0.011), explaining 34.1% of the variance (R² = 0.341). Although each dimension does not have a significant partial effect, influencer credibility collectively plays a role in shaping Generation Z’s purchase intention. These findings suggest that influencer marketing is an effective strategy for increasing purchase intention on Tokopedia.